Peningkatan Kompetensi Kinerja Sumber Daya Manusia PTK di Mts Al-Washliyah Kolam - Tengku Darmansah; Afrizal Rambe; Ghadief Hanbal Silalahi; Yuda Nur Diamsyah; Ilham Martua Hasibuan (Student Research Journal, 2024)
Human resource development (HRD) is a key factor in improving the competitiveness of education, especially in the era of globalisation and the industrial revolution 4.0. This article aims to examine the role of improving HR competencies in influencing the performance of educators and education personnel at Mts Al-Washliyah Kolam. The research method used is descriptive with data collection techniques through observation, interviews, and documentation. The results showed that development programmes such as professional workshops and collaborative learning communities significantly improved the ability and professionalism of educators. This finding confirms the importance of competency development in creating an innovative and effective learning environment. This article is expected to serve as a reference for policy makers and education practitioners in designing more effective HR development programmes, as well as providing insights into the importance of synergy between education and training in improving the quality of education in Indonesia.